The Effect Of Muscle Energy Technique (MET) on Range of Motion (ROM) Knee Joint in Patients Postoperative Posterior Cruciate Ligament Reconstruction (PCLR) Hamstring Graft : A Case Study - Sobariyah, Ana Maratus; Efendi, Elif Nur; Perdana, Suryo Saputra (Universitas Muhammadiyah Surakarta, 2022)
Introduction: Posterior crusiate ligament reconstruction (PCLR) surgery is an operating method to replace PCL ligaments with other materials (graft). PCLR postoperative rehabilitation focuses on reducing pain, swelling, stiffness, instability, regaining range of motion (ROM), muscle strength, and normal functional activity. Restoring the range of motion (ROM) postoperatively of PCL reconstruction is an important aspect of normal human functioning.Case Presentation: A male is a 38-year-old language tutor with a height of 150 cm and a weight of 75 kg. Patients condition of motion pain in the knee and limitation of movement flexion knee sinistra after PCLR hamstring graft surgery since December 2021. The patient feels difficulty and pain at the time of the sitting position to the stand, stand for a long time and walk a long distance. the patient can already carry out his work even with a sitting position and the legs remain straight. Currently, patients undergo routine physiotherapy at the clinic practice physiotherapy Magetan 3x / week. The patient's current condition is experiencing limited mobility when bending the knee.Management and Outcome: The intervention used muscle energy technique (MET) for 3x/week in 4 weeks. The disorder is a limitation of movement for knee flexion. Evaluation carried out using a goneometer instrument to measure the range of motion (ROM)Conclusion: It can be concluded that in this case, after providing physiotherapy intervention in the form of MET, it has an effect on the increase knee joint ROM in patients postoperative PCLR.